Settlement of Lime-Cement Stabilized Soft Clay: A Numerical Modeling Study - Salem , Tarek N.; El-Kady , Mahmoud S.; Abdelbaset , Ahmed M.; Ghoneim, Amr G.; Katunský, Dušan; Konovalov , Denis; Švajlenka , Jozef; El-Feky , Mohamed H. (Salehan Institute of Higher Education, 2026)
This study aims to quantify settlement uncertainty of strip footings on stabilized soft clay under multi-parametric variations to improve geotechnical foundation design. A three-dimensional numerical model was developed using ADINA to simulate full-scale strip footings resting on treated soft clay. Finite Element Analysis was conducted by systematically varying four governing parameters: footing width, treated soil thickness, treated extension width, and footing embedment depth. Parametric analyses were performed using normalized design ratios to evaluate settlement sensitivity and soil–structure interaction behavior. The results indicate that increasing the ratios of treated thickness to footing width, treated extension width to footing width, and embedment depth significantly reduces total settlement and enhances stress redistribution within the improved zone. Sensitivity assessment reveals that treated thickness and extension width are the most influential parameters in controlling settlement performance. The novelty of this research lies in quantifying settlement sensitivity through dimensionless design ratios within a unified numerical framework, providing a practical basis for optimizing treated zone dimensions. The findings contribute to a more efficient and sustainable foundation design by minimizing excessive material use while maintaining structural performance, offering economic and environmental benefits.